2014
DOI: 10.7184/cuid.2014.39.13
|View full text |Cite
|
Sign up to set email alerts
|

Perfil de pacientes estomizados: revisão integrativa da literatura

Abstract: An analysis on the profile of ostomy, multicenter studies that portray the specific characteristics of these patients, contributes to meeting their real needs and the targeting of public policies and health to improve the quality of life for these clients. This study aims to investigate the scientific profile about ostomy patients in the period [2004][2005][2006][2007][2008][2009][2010][2011][2012]. It is an integrative literature review performed by an electronic search in databases: Lilacs, Scielo, and Bdenf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
15

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 5 publications
4
18
0
15
Order By: Relevance
“…Neste estudo observou-se que a maioria dos pacientes tinham colostomia em relação à ileostomia, corroborando com a maioria dos estudos de caracterização clínica de pacientes com EIE (26,27) . No decorrer dos meses de janeiro a março de 2012, várias instituições de saúde brasileiras realizaram cerca de nove mil cirurgias reparadoras do aparelho digestivo, destas, um terço resultou na realização de uma EIE (colostomia ou ileostomia), e parte dos pacientes foi submetido ao procedimento cirúrgico que se fez necessário o uso de equipamento coletor de efluentes (28) .…”
Section: Resultsunclassified
“…Neste estudo observou-se que a maioria dos pacientes tinham colostomia em relação à ileostomia, corroborando com a maioria dos estudos de caracterização clínica de pacientes com EIE (26,27) . No decorrer dos meses de janeiro a março de 2012, várias instituições de saúde brasileiras realizaram cerca de nove mil cirurgias reparadoras do aparelho digestivo, destas, um terço resultou na realização de uma EIE (colostomia ou ileostomia), e parte dos pacientes foi submetido ao procedimento cirúrgico que se fez necessário o uso de equipamento coletor de efluentes (28) .…”
Section: Resultsunclassified
“…It is noticed that the person with chronic illness needs to share their living and experiences, and the presence of friends constitutes an empathic environment, which favors the reduction of the anxiety of the person with the ostomy, through the manifestations of affection, understanding and solidarity. 4,12,18 In the presence of friends, a facilitator is available so that the person with a ostomy can gradually achieve security in order to return to their social activities and continue the goals of their life.…”
Section: (In) Availability Of Professionals From Health Institutionsmentioning
confidence: 99%
“…It is considered in this case that the financial support received can be a significant support for the adjustment to this new condition of life, due to the increase in expenses with medicines, supplies for the care of the ostomy, among others. 19 It is emphasized that besides the opportunity to receive from the friends the emotional and material support 2,[6][7][8]12,[17][18][19] counting as spiritual support is another fundamental aspect for people living with a cancer or an oedematum, because they can find in spirituality relief for suffering and assistance to face the adversities of everyday life, through the comfort of words of faith and hope. 7,20 It corroborates with these findings research on the social network of support for men with prostate cancer that showed belief in God as an important factor for overcoming the negative feelings arising from illness and for cancer survival.…”
Section: (In) Availability Of Professionals From Health Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…They can occur in all stages of life, from birth, childhood, adolescence, to adulthood, including the elderly. 4 The surgical process for the manufacture of the ostomy is considered traumatic, since it causes severe alterations in the lifestyle of the individual, which demand a singular and specialized assistance. 5 The implementation of this new path, along with elimination changes, is accompanied by challenges, changes in daily life, changes in eating habits, reconstruction of beliefs and values, and consequent alteration in the quality of life of these patients, especially in the physical and social dimensions.…”
Section: Introductionmentioning
confidence: 99%